Answer:
![x^(2)-6x+8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1p4ddmjdyrj4w4o4yziod39hs6b42p06jr.png)
Explanation:
Given:
Binomial is
.
In FOIL method, we first multiply the first term of each binomial. First terms are
and
.
⇒
![x* x=x^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gmtvulxr3h6z736j6z4gzkd0smr659zl6i.png)
Next, we multiply the outer terms. Outer terms are
and -4.
⇒
![x* -4=-4x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r0em7a8ejcgxo0zal8xgpmdr49l0iireek.png)
Next, we multiply the inner terms. Inner terms are -2 and
.
![-2* x=-2x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ltumcglz4173evxvku858eat5bn5pxnox8.png)
Lastly, we multiply the last terms of each binomial. Last terms are -2 and -4.
![-2* -4=8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mw24j1f9k9qjl71ojyy9gbi3e0u9cytdce.png)
Now, we add all the results to get the answer.
Therefore,
![(x-2)(x-4)=x^(2)-4x-2x+8=x^(2)-6x+8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xm8njazgrw0au82s3nea62pgpguf6qf957.png)